Política Nacional de Saúde Integral de Lésbicas, Gays, Bissexuais, Travestis e Transexuais: Reflexões sobre a assistência à saúde - Silva, Jedison Feliciano (2019)
Introduction: Historically, lesbian, gay, bisexual, transvestite and transgender populations have been positioned in a place of restriction of rights. Emphasizing the health field, studies that investigate the care practices directed to these individuals, point out that the accessibility of these groups to health is permeated by a series of inequities. Objective: Understand the health care of lesbian, gay, bisexual, transvestite and transgender people in Paraiba. Methodological approach: Exploratory and descriptive study of qualitative approach, developed in the reference services of the State of Paraíba. For the collection of information, a documentary survey of the Health Plans, Annual Health Schedule and Annual Management Report, from 2013 to 2018, was conducted, as well as semi-structured interviews with professionals and users of the services. The formation of the study group was determined by purposeful sampling and the number of collaborators was based on the Theoretical Saturation Method. Thus, 12 professionals and 30 users were interviewed. The empirical material resulting from the documentary and speech analysis was analyzed jointly, considering the principles concerning data triangulation in order to identify convergent, divergent or complementary points. Results: The data set, submitted to content analysis, originated the following relevance categories: Health services and actions; Educational practices; Mobilization, articulation, participation and social control activities; and Monitoring and evaluation of health actions. Conclusions: There are advances in trying to meet the health demands of the LGBT segment, verified from the inclusion of targets related to this public in the analyzed documents. In practical terms, however, it is observed that such advances are restricted to specialized services for transvestites and transsexuals and that identified health actions favor clinical practices. Likewise, the lack of permanent education and health education practices, visualized in this study, tend to corroborate the institutional prejudice and sexual orientation / gender identity in SUS services. Changes in this context go through the reorganization of health care models, in order to deepen the discussion about issues considered fundamental for the health promotion of these subjects.